A Needs Analysis for Scratch-Based Digital Media in Junior High Coding and Artificial Intelligence Education - Faizal Mutaqin; Taufiqulloh Taufiqulloh; Dewi Amaliah Nafiati (Research Horizon, 2026)
The development of interactive digital learning media is essential to support coding and Artificial Intelligence (AI) education at the junior high school level. This study aims to analyze the needs for developing scratch-based interactive digital learning media that can enhance student engagement and facilitate a more practical understanding of coding and AI concepts. This research employed a qualitative descriptive approach. The subjects included an informatics teacher and eighth-grade students at a public junior high school. Data were collected through classroom observations, in-depth interviews with teachers, and an analysis of school facilities and learning conditions. The instruments used were observation sheets and interview guides that had been validated by experts. The results of the needs analysis indicate that coding and AI learning remain predominantly theoretical, lack interactive digital media support, and have not yet optimized the use of computer laboratory facilities. Both teachers and students require digital learning media that are visual, easy to use, and capable of providing project-based learning experiences. Based on these findings, the development of interactive digital learning media using Scratch is necessary to align with the characteristics of junior high school students and to support the achievement of learning competencies in coding and artificial intelligence.